Virtual and Augmented Reality: Prospects in Radiology Education and Training - Yordanov, Mariana (British Journal of Healthcare and Medical Research, 2024)
Purpose: This article reviews the applications of virtual and augmented reality in medical education and training in the field of radiology. The article studies existing scientific literature on the uses of virtual and augmented reality in radiology education and training and their benefits. Materials and methods: This article use available scientific literature on VR and AR applications in radiology education and training from PubMed, Google Scholar and ScienceDirect. Results: Virtual and augmented reality offer specialized medical and commercial tools for radiology education and training in imaging and interventional radiology. They include VR games, life-sized simulation environments, computerized sensor tables, head-mounted devices and others. Tests and studies of VR and AR technologies for students and residents show promising results for educational value and improved educational outcomes. Nevertheless, there are many challenges in the adoption of virtual and augmented reality for medical education and training. Conclusions: The prospects of virtual and augmented reality in radiology education and training are promising but more scientific studies are needed to ensure their benefits.